Evolution of Microstructure and Mechanical Properties of Steam Generator Material After Long-Term Operation in Nuclear Power Plant - David Slnek; Mária Dománková; Marek Adamech; Jana Petzová; Katarína Bártová; Marek Kudláč; Matúš Gavalec (Metals)
The microstructural evolution and mechanical properties of WWER 440 steam generator steel GOST 22K after long-term operation were thoroughly examined in this study. The samples were taken directly from a steam generator using the small punch test method. The uniqueness of these samples lies in the fact that they were real operating materials used in a nuclear power plant with different years of operation. The microstructure was characterized using optical microscopy and transmission electron microscopy supplemented by selective electron diffraction and semi-quantitative chemical microanalysis. It was found that with the prolongation of the operation time of the steam generator, the density of carbides increased slightly, which was reflected in a decrease in the mean distance between particles, but these differences were very small, which indicates the microstructural stability of GOST 22K steel. The stability of this steel was also confirmed by measuring its mechanical properties, which changed only minimally depending on the years of operation. The tensile strength values were in the range of 508 to 579 MPa. In the case of the ductile-to-brittle transition temperature (DBTT), a slight increase was found after 6 years of operation. The DBTT did not change significantly with subsequent operation.